Pain processing in early life - Fitzgerald, Maria (Henry Stewart Talks, 2010)
The immediate problem of childhood pain, The long term impact of childhood pain, How can pain be measured in infants?, Cortical pain responses, Nociceptive reflexes, What drives the 'tuning' or maturation of dorsal horn neuronal properties and nociceptive reflexes?, Can immature pain circuits respond to persistent injury or inflammation?, Tissue damage and inflammation, Central sensitization, Neuropathic pain development, Does early pain experience shape adult pain perception?, Pain memory